Validitas dan Praktikalitas E-modul Sifat Koligatif Larutan Berbasis Guided Discovery Learning untuk Kelas XII SMA - Monita Sari; Yerimadesi Yermadesi (Edukimia, 2021)
Guided discovery learning based E-module is a teaching material in electronic to support independent learning that follow the stages of guided discovery learning model. The development research was conducted to develop and analyse the validity and practicality of this e-module on colligative properties of solution material for class XII high school chemistry learning. The type of research is educational design research using the Plomp development model consisting of (1) preliminary research, (2) prototyping stage, (3) assessment phase. The e-module was validated by eight validators who are four UNP chemistry lecturers and four chemistry teachers using an instrument in the form of validity questionnaire, while the practicality test was carried out at SMA N 8 Padang by 27 students and three teachers with an instrument in the form of a practicality questionnaire. The questionnaire analysis was performed using the Content Validity Ratio (CVR) for content validation and Aiken V formula for construct validation and practicality. From the results, the data indicate that the solution based colligative properties e-module based on guided discovery learning for chemistry learning in class XII senior high school has valid and practical values.